2019
DOI: 10.3390/nano9030382
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Hydrogen Damage Using MoS2 Coating on Iron Surface

Abstract: The prevention of hydrogen penetration into steels can effectively protect steels from hydrogen damage. In this study, we investigated the effect of a monolayer MoS2 coating on hydrogen prevention using first-principles calculations. We found that monolayer MoS2 can effectively inhibit the dissociative adsorption of hydrogen molecules on an Fe(111) surface by forming a S–H bond. MoS2 coating acts as an energy barrier, interrupting hydrogen penetration. Furthermore, compared with the H-adsorbed Fe(111) film, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The MoS 2 layer usually exhibits a good adhesion performance because the sulfur atom can bond tightly to a metal surface. Li et al 71 analyzed the hydrogen transfer energy between a MoS 2 layer and an Fe (111) surface by spinpolarized density function theory (DFT). It was found that the hydrogen adsorption energy on the surface increased from 0.55 to 1.26 eV, which proves that MoS 2 can be used as a hydrogen barrier.…”
Section: Carbides Silicon Carbide (Sic)mentioning
confidence: 99%
“…The MoS 2 layer usually exhibits a good adhesion performance because the sulfur atom can bond tightly to a metal surface. Li et al 71 analyzed the hydrogen transfer energy between a MoS 2 layer and an Fe (111) surface by spinpolarized density function theory (DFT). It was found that the hydrogen adsorption energy on the surface increased from 0.55 to 1.26 eV, which proves that MoS 2 can be used as a hydrogen barrier.…”
Section: Carbides Silicon Carbide (Sic)mentioning
confidence: 99%
“…Deyab and Keera explored [18], 1.0 M H2SO4 corrosion prevention for carbon steel was explored using a coating system containing nano -TiO2 particles of varying sizes (10, 50, 100, and 150 nm). These nano-TiO2 particles increased the corrosion resistance of coatings In 2015 Motonori Tamura [19] Stated that coating with Al2O3, TiC, or TiN reduced the hydrogen permeability of the 316L austenitic stainless steel twice as much as the uncoated substrates, Xinfeng Li and others in 2019 studied the action of surface roughne ss on the hydrogen blistering in steel, It was found that ground s urfaces that have greater roughness showed compressive residual stress in compression to polished surfaces the ground test specimens offers less sensibility to hydrogen blisters compared with the polished test specimens [20] in 2020 Muhammad Wasim, and Milos [21] studied the influence of hydrogen penetration of low-carbon steel at macro-, micro-, and nanoscales in the hydrogen-rich acidic atmosphere. The results proved that there is a directly proportional relationship between the concentration of hydrogen and corrosion rate with increasing charging time,…”
Section: Introductionmentioning
confidence: 99%
“…It has been known for about a century that hydrogen contamination causes severe degradation in the mechanical properties of metals [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. This phenomenon is generally termed as “hydrogen embrittlement” (HE).…”
Section: Introductionmentioning
confidence: 99%